Peran Kecerdasan Emosional Guru dalam Menciptakan Lingkungan Belajar yang Inklusif - Rianita Malikhotul Faoziah; Ellen Prima (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Teachers' emotional intelligence is one of the important factors in creating an inclusive learning environment that is able to accommodate the diversity of students' characteristics, abilities, backgrounds, and needs. This article aims to examine the role of teachers' emotional intelligence in supporting the implementation of inclusive learning in school settings. The method used in this study is a literature review by analyzing various relevant scientific sources related to emotional intelligence and inclusive education. The findings indicate that teachers with strong emotional intelligence are more capable of understanding students' feelings and needs, building positive communication, managing conflicts effectively, and creating a safe and comfortable learning atmosphere for all students.